Bio-ecological study on Aceh coast to determine mangrove ecosystem restoration areas suitability - Meilinda Suriani Harefa; Nur Rohim; Imam Pramuja; Putri Ramadayanti Harahap; Suciati Agustin; Kamaluddin Siregar; Jonatan Pardamean Sitanggang (Depik, 2023)
Mangrove forests in Aceh are significant because of their roles in ecological, socio-economic, and socio-cultural aspects. Mangrove restoration efforts must be based on adequate land assessment and regular evaluation of the viability of planted mangroves. Therefore, this study aimed to analyze the bio-ecological characteristics of mangrove planting locations and evaluate land suitability in the restoration areas in Aceh Besar (Layeun Village) and Aceh Jaya (Babah Ie, Ujong Sudeun and Keude Unga Villages). This study was conducted in the YAGASU restoration area in Aceh Besar and Aceh Jaya Regencies in September 2022. The primary data consisted of the physicochemical characteristics of the environment, biodiversity, land suitability index, and plant survival rates after 3- 6 months planted. Data were analyzed using correlation, principal component analysis (PCA), cluster analysis (CA), descriptive statistics, and land suitability index. The result showed that the physical-chemical parameters of the environment are suitable for supporting the growth of mangroves and the livelihoods of various communities. In the study areas, the communities include 8 mangroves, 15 fish, 19 benthic, 11 zooplankton, and 22 phytoplankton species. Layeun, Ujong Sudeun, and Keude Unga Villages were found to have better land suitability than Babah Ie Village. However, an evaluation of the results of planting monitoring showed that Layeun has the highest survival rate compared to the other three villages. The results showed that pests, including buffalo and crustaceans, as well as sea waves, and the duration of the tides inundating the water are the main factors causing mangrove mortality.Keywords:Mangrove restorationSuitabilityBio-ecological